How does lymph node yield affect survival outcomes of stage I and II colon cancer? - Chi Chung Foo; Clement Ku; Rockson Wei; Jeremy Yip; Julian Tsang; Toi Yin Chan; Oswens Lo; Wai Lun Law (World Journal of Surgical Oncology, 2020)
Abstract Background According to the American Joint Committee on Cancer staging for cancer of the colon, a minimum of 12 lymph nodes (LN) has to be sampled for accurate staging. This has bearing on the long-term prognosis and the need for adjuvant chemotherapy. The aim of this study was to revisit the association of lymph node yield and the long-term survival in patients with stages I and II, i.e. node-negative, colon cancer. Method Consecutive patients who underwent elective or emergency curative resections for cancer of colon between the years 2003 and 2012 were retrospectively reviewed. Only patients with stage I or II diseases (AJCC 8th edition) were included. They were analysed in three groups, LN<12, LN12-19 and LN≥20. Their clinic-pathological characteristics were compared. The disease-free (DFS) and overall survival (OS) were estimated with the Kaplan-Meier method and compared with the log-rank test. Results There was a total of 659 patients included in the analysis. Twelve or more LN were found in 65.6% of the specimens. The mean follow-up was 83.9 months. LN≥20 had significantly better DFS (p = 0.015) and OS (p = 0.036), whereas LN<12 had similar DFS and OS when compared to LN12-19. The advantage in DFS and OS were mainly seen in those with stage II diseases. A lymph node yield of greater than 20 was one of the predictors of favourable DFS, hazard ratio 0.358; 95% CI 0.170–.756, p = 0.007. Conclusion The lymph node yield had a significant association with survival outcomes. A lymph node yield of 20 or more was associated with better survival outcomes. On the other hand, lymph node yield less than 12 was not shown to have inferior survival outcomes when compared to those between 12 and 19.